2018
DOI: 10.5137/1019-5149.jtn.23296-18.3
|View full text |Cite
|
Sign up to set email alerts
|

Use of the intraoperative ultrasonography in intradural spinal tumor surgery

Abstract: neurosurgeons to use it in intradural spinal tumor surgery (4-7). The main contribution to surgery includes detection of the exact tumor localisation and the resection amount (6-9). A recent study by Harel and Knoller showed that IOUSG changed the course of surgery in 63% of the cases (6).Toktas et al. reported that the sensitivity of IOUSG for the determination of the extent of resection was up to 92% and that IOUSG is effective in the identification of tumor boundaries and the protection of spinal cord vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Treatment of these pathologies is surgical, and in recent years effective results have resulted in tumor surgery from the use of technological innovations. Intraoperative neuromonitorisation (IONM), magnetic resonance (MR) tractography, and ultrasonography (USG) have been used for safe and maximum surgical resection (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Furthermore, surgery under the guidance of Sodium-fluorescein (Na-fluorescein) has earned a place in neurosurgery for tumor resection and tumor volume reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of these pathologies is surgical, and in recent years effective results have resulted in tumor surgery from the use of technological innovations. Intraoperative neuromonitorisation (IONM), magnetic resonance (MR) tractography, and ultrasonography (USG) have been used for safe and maximum surgical resection (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Furthermore, surgery under the guidance of Sodium-fluorescein (Na-fluorescein) has earned a place in neurosurgery for tumor resection and tumor volume reduction.…”
Section: Introductionmentioning
confidence: 99%
“…As per Friedman et al, intraoperative ultrasound proved highly effective in documenting and localizing the tumor before entering the dural space without significantly affecting the procedure length or surgical risk [ 11 ]. Also, another study confirmed the high effectiveness of using the Intraoperative Ultrasonography in Intradural Spinal Tumor, where In 62 out of 69 cases, Pre-durotomy intraoperative ultrasound successfully delineated tumor boundaries and facilitated adequate laminectomy, achieving a success rate of approximately 90 % [ 20 ]. But in our case, we did not use the ultrasound, because we really did not expect such a phenomenon, and after opening the dura, we did not find the tumor in its place completely.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, our surgical approach prioritizes maximal tumour debulking while meticulously preserving neurological function, aligning with the primary goal of improving patient quality of life and managing symptoms effectively. Supplementary intraoperative techniques such as ultrasonography can also be implemented to assist in deciding the extent of laminectomy, durotomy and resection of the lesion [ 13 ].…”
Section: Discussionmentioning
confidence: 99%